Solvent-free glycerol transesterification with propylene carbonate to glycerol carbonate over a solid base catalyst - Kondawar, Sharda; Rode, Chandrashekhar (Energy & Fuels, 2017)
Glycerol transesterification using propylene carbonate (PC) to glycerol carbonate.(GC) could be efficiently performed under solvent-free 'conditions 'wing solid base as catalysts involving non-noble metal oxide in combination with hydrotalcites (HTs). Among all of the catalysts studied for transesterification, the best result was obtained over a calcium-doped hyclrotalcite (Ca-FIT) catalyst, giving 84% conversion of glycerol and almost complete. GC selectivity. The crystal structure of HT was modified by incorporation of Ca and La into FIT, as revealed by X-ray diffraction studies. The temperature-programmed desorption of carbon dioxide study confirmed the presence of the highest basic site density in terms of 1.94 mmol of CO2 desorbed/g of catalyst, responsible for its higher transesterification efficiency of the Ca-HT catalyst. The Fourier transform infrared spectroscopy study showed peaks at 3036 and 3042 cm(-1) for Ca -HT and lanthanum-doped hydrotalcite (La -HT), respectively, confirming the presence of hydrogen bonding between water and interlayer carbonate anions responsible for abstracting proton from the primary hydroxyl group of glycerol to attack over carbonyl carbon of PC. The presence of intercalated carbonate ions is also confirmed by the Raman study, in both PIT and ca-HT catalysts and even after use of the Ca HT catalyst. The thermogravimetry-differential thermal analysis study evidenced the higher thermal stability of the Ca -HT (T-4 = 765 degrees C) catalyst than that of parent HT with a Mg/Al ratio of 3:1 (T4 = 630 degrees C). Various process conditions, such as the temperature, molar ratio of glycerol/PC, and catalyst loading, significantly influenced conversion and selectivity of glycerol: and GC, Tespectively.